Beneficios socioeconomicos y condiciones habilitadoras del manejo forestal comunitario en Guatemala y Nicaragua. - Stoian, D.; Rodas, A.; Arguello, J. (Bioversity International, 2017)
Policy Brief in relation to the ADA-funded project "Community Forestry in Mesoamerica for Conservation and Rural Development".